Intercalation of nanostructured CeO2 in MgAl2O4 spinel illustrates the critical interaction between metal oxides and oxides. Issue 7 (31st January 2018) - Duan, Xinping; Wen, Zhaojun; Zhao, Yuxin; Zhou, Junfu; Fang, Huihuang; Cao, Yanning; Jiang, Lilong; Ye, Linmin; Yuan, Youzhu
Abstract : Critical interaction of metal oxide-oxides: Intercalation of nanosized CeO2 in MgAl spinel helps develop and maximize reactive oxygen storage/release capabilities. Abstract : Heterogeneous catalytic oxidation arises from the prerequisite oxygen activation and transfer ability of metal oxide catalysts. Thus, engineering intercalated nanounits and heterophase metal oxide structures, and forming interstitial catalyst supports at the nanoscale level can drastically alter the catalytic performances of metal oxides. This is particularly important for ceria-based nanomaterial catalysts, where the interactions of reducible ceria (CeO2 ) and nonreducible oxides are fundamental for the preparation of enhanced catalysts for oxygen-involved reactions. Herein, we intercalated nanostructured CeO2 in the bulk phase of magnesium aluminate spinel (MgAl2 O4, referred to as MgAl), produced the interstitial effect between CeO2 nanoparticles and MgAl crystallites, thus boosting their oxygen transfer and activation capability. This nanoscaled intercalation engineering significantly enhanced the number and quality of tight contact points between the nanostructured CeO2 and MgAl units. Therefore, the oxygen storage/release capability (OSC) is exceptionally improved as revealed by various characterizations and catalytic carbon oxidation reaction. A mechanism similar to the Mars–van Krevelen process at the nanoscale level was invoked to explain the catalytic oxidation mechanisms. The reactive oxygen species of gaseous O2 originate formed the bulk of the as-obtained nanomaterial, where strong interactions between the CeO2 and MgAl components occured, which were subsequently released and diffused to the catalyst-interface at elevated temperatures. Silver supported on Ce–MgAl produced an approximately 4-fold higher concentration of active oxygen species than Ag/MgAl, and gives the optimum low-temperature oxidation at 229 °C. This study verifies the importance of the redox performance of ceria-spinel with enhanced OSC, which validates that the arrangement of contacts at the nanoscale can substantially boost the catalytic reactivity without varying the microscale structure and properties of spinel.